A study on the grey relation analysis between the overall performance and individual event scores of international elite trampolinists - Zhu, Xinyu; Wang, Lejun (Frontiers in Sports and Active Living, 2024)
This study applies grey relational analysis to assess the relationship between individual trampoline event scores and overall performance of top male and female athletes in the 2020 Tokyo Olympics. Analyzing execution, horizontal, difficulty, timing of flight, and total scores, results show males excelled significantly in difficulty, timing, and overall performance, while execution and horizontal scores were comparable. For males, timing of flight (excluding outliers) had the greatest influence on total score, followed by difficulty and execution. In females, difficulty dominated, followed by timing and horizontal, with execution least impactful. The study highlights the primary roles of timing and difficulty scores in overall trampoline performance, with gender variations in score contributions. The findings illuminate the interplay of score components, offering a theoretical framework for targeted trampoline training. For international athletes, key considerations include boosting height index for a robust trampoline foundation; tailoring difficulty levels to athletes' abilities while adhering to scoring rules, without sacrificing technical prowess; and sustaining training to refine quality and stability of routines.